2020
DOI: 10.1002/bjs5.50261
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of incisional hernia after midline laparotomy with prophylactic mesh reinforcement: a meta-analysis and trial sequential analysis

Abstract: Background: Incisional hernia is a frequent complication after abdominal surgery. The aim of this study was to assess the efficacy of prophylactic mesh reinforcement (PMR) after midline laparotomy in reducing the incidence of incisional hernia.Methods: A meta-analysis was conducted following PRISMA guidelines. The primary outcome was the incidence of incisional hernia after follow-up of at least 12 months. Secondary outcomes were postoperative complications. Only RCTs were included. A random-effects model was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 35 publications
(65 reference statements)
1
33
2
Order By: Relevance
“…These authors recommended the use of surgical mesh in some high-risk patients and suggested that individual risk factors should be taken into account when selecting patients who would most benefit from mesh insertion. Another recent metaanalysis and sequential analysis of 12 RCTs involving 1815 patients by Jairam et al [34] reported that prophylactic mesh reinforcement using an onlay or retromuscular technique after midline abdominal surgery significantly decreased the rate of occurrence of IH in high-risk patients and that onlay mesh reinforcement could become the standard treatment for high-risk patients undergoing midline laparotomy.…”
Section: Discussionmentioning
confidence: 99%
“…These authors recommended the use of surgical mesh in some high-risk patients and suggested that individual risk factors should be taken into account when selecting patients who would most benefit from mesh insertion. Another recent metaanalysis and sequential analysis of 12 RCTs involving 1815 patients by Jairam et al [34] reported that prophylactic mesh reinforcement using an onlay or retromuscular technique after midline abdominal surgery significantly decreased the rate of occurrence of IH in high-risk patients and that onlay mesh reinforcement could become the standard treatment for high-risk patients undergoing midline laparotomy.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review concluded that mesh reinforcement is safe and effective at early-to-midterm assessment [73].…”
Section: Prophylactic Mesh Augmentation In Patients At Increased Riskmentioning
confidence: 99%
“…The main complication after laparotomy is incisional hernia (IH), which has an incidence of 10-23% (1), although this can increase to up to 40% in speci c risk groups (2). IH is often asymptomatic; however, in some patients, it is a signi cant a cause of morbidity (pain), in addition to having a negative effect on the patient's quality of life and body image (3).…”
Section: Introductionmentioning
confidence: 99%
“…The actual impact of prehabilitation on the reduction of IH has not yet been determined, and in patients undergoing emergency surgery, prehabilitation is not possible. Therefore, at present, the options for reducing the incidence of this complication focus on the use of prophylactic meshes (2)(3)(6)(7)(8)(9)(10)(11) and on modifying the laparotomy closure technique. Evidence indicates that the use of prophylactic mesh is a safe and effective procedure in both clean and clean-contaminated surgery, but there is insu cient evidence for contaminated or dirty surgeries (12)(13)(14); nonetheless, its use has not yet become widespread.…”
Section: Introductionmentioning
confidence: 99%